Time and Alcohol Do Not Change Everything: How Intoxicated Witnesses Perceive Aggression in Intimate Partner Violence - Hildebrand Karlén, Malin (Journal of interpersonal violence, 2021)
Although alcohol-intoxicated witnesses to violent crimes are common, research on how alcohol affects witnesses’ perception of aggression is sparse. In the present study, it was investigated whether different levels of intoxication altered how severe witnesses perceived aggression displayed by involved parties in an intimate partner violence (IPV) scenario to be. An experimental mixed-groups design 3 (sober vs. moderate vs. high breath alcohol concentration [BAC]) x 2 (immediate vs. one week delayed interview) was used. Socially drinking men and women (n = 137; 67 and 70, respectively) were randomized to an alcohol condition (0.8 g/kg adjusted to 0.75 g/kg for women, divided into two intoxication groups: moderate ≤0.08 and high ≥0.08) or a control condition (juice). They were also randomized into a direct interview condition or a delayed interview condition. In a laboratory setting, they consumed drinks and viewed an IPV scenario on film. During their interview, the participants rated how severe they perceived the involved parties’ aggression to be. Inter alia, participants in the high BAC group perceived both parties’ physically aggressive behavior as comparatively less severe than the sober and moderately intoxicated witnesses did. The high BAC group also perceived the IPV scenario as less unpleasant than the other two groups, and they maintained this perception over time and repeated interviews. A BAC level of ≥0.08 was required to significantly lower witnesses’ perceived severity of physical aggression, possibly caused by alcohol’s anxiety-dampening effect as well as its impairing effect on cognitive processing capacity over this level of intoxication. That alcohol intoxication at (or over) such a BAC level makes witnesses perceive physical aggression as less severe and less unpleasant, and also that such an altered perception holds over time and repeated interviews, is important for legal practitioners to be aware of when handling intoxicated witnesses to violence. Therefore, this issue warrants further investigation.